Study of electronic transport parameters on the heterojunction of AlGaN/GaN, grown on Sapphire: two layer model - Shrestha, Sanju; Shakya, Ambika; Sarkar, C K (BIBECHANA, 2018)
In spatially confined system such as heterojunction of high and low band gap material, carriers are transferred from higher band gap to the lower band gap. It causes the band bending and the formation of a triangular quantum well at the junction. Such system behaves as quantum-two dimension (Q2D) system because the carriers are free to move on a plane, perpendicular to the junction. Mobility of such quantized system is very high as compare to the bulk system due to the reduction of various scattering mechanisms. GaN is a very useful material. However, a non availability of single crystalline form of GaN and perfectly matched substrates are always problems for GaN. Hence GaN, grown on a substrate such as sapphire is having a very large dislocations at the interface. Such interfacial layer significantly affects the transport parameters of the material, where the transport properties are highly dominated by scattering due to dislocations. The authors have calculated the mobilities of AlGaN/GaN, a heterojunction considering the GaN, grown on Sapphire with reference to the two layer model of Look, in which the 2nd layer is the dislocation layer of GaN and the 1st layer is the junction of AlGaN/GaN where carriers are in the form of two dimensional electron gas (2D EG). The obtained calculated results are also compared with the experimental results as obtained by Sibel Gokden et al. It is observed that the nature of the curve is found to be in agreement with the experimental curve when the ratio of the thicknesses is taken to be 1:1. BIBECHANA 16 (2019) 137-144